2024
DOI: 10.3389/fpubh.2024.1366378
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of vaccinators about expanded programs on immunization: a cross-sectional study

Sunia Azhar,
Laiba Rashid,
Taskeen Islam
et al.

Abstract: IntroductionThe periodic evaluation of knowledge, attitudes, and practices (KAP) of healthcare workers, including vaccinators, concerning expanded programs on immunization (EPI) is very crucial for a better healthcare system. This study was carried out to assess the KAP of vaccinators about the EPI, including cold storage of vaccines and their practices related to vaccine cold chain management.MethodA cross-sectional study was conducted from January 2022 to June 2022 among registered vaccinators in the twin ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Immunization stands as one of the most successful and cost-effective health interventions against infectious diseases, particularly in the context of epidemic disease prevention and control 2 . Research has shown the significant advantages of vaccination, encompassing decreased disability, hospital admissions, healthcare costs, and mortality rates 3 5 . However, recent years have witnessed a concerning decline in public trust in vaccines, accompanied by rising rates of vaccine hesitancy 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Immunization stands as one of the most successful and cost-effective health interventions against infectious diseases, particularly in the context of epidemic disease prevention and control 2 . Research has shown the significant advantages of vaccination, encompassing decreased disability, hospital admissions, healthcare costs, and mortality rates 3 5 . However, recent years have witnessed a concerning decline in public trust in vaccines, accompanied by rising rates of vaccine hesitancy 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%